2008
DOI: 10.1253/circj.72.476
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Distributions of Peptides Derived From Proadrenomedullin in Left-to-Right Shunt Pulmonary Hypertension of Rats

Abstract: ulmonary hypertension (PHT) is a common and serious complication of left-to-right shunt congenital heart disease (CHD), and the risk and mortality of cardiac surgery in CHD patients complicated with serious PHT are significantly increased. However, the pathogenesis of PHT remains unclear so far.Adrenomedullin (ADM), a potent vasodilation peptide, was originally isolated from human pheochromocytoma and is thought to have an autocrine or paracrine action, playing an important role in the regulation of vascular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…This is consistent with the results of our previous research that the left‐to‐right shunt rats displayed more brown granules of ADM and PAMP in the pulmonary arterial wall (Cuifen et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results of our previous research that the left‐to‐right shunt rats displayed more brown granules of ADM and PAMP in the pulmonary arterial wall (Cuifen et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…Among them, ADM and adrenotensin (ADT) are distributed throughout the vascular smooth muscle cell layer, whereas proADM N-terminal 20 peptide (PAMP) is found within the tunica adventitia. ADM stimulates blood vessel dilation and inhibits smooth muscle cell proliferation and migration (6,7). ADM activates the potassium channel in smooth muscle cells to enable cellular hyperpolarization (8).…”
Section: Introductionmentioning
confidence: 99%
“…Gumusel et al reported that ADM induces endothelium-dependent vasoconstriction and elevation of blood pressure [5,6] . In a rat model of pulmonary hypertension, Cuifen et al reported that ADM and ADT have opposite effects on vasoactivity and showed reciprocal inhibition in their release [7] . In Qi's study, ADT induced an increase in the concentration of medium ir-ADM [8] .…”
Section: Introductionmentioning
confidence: 99%